Exploring Transformational Leadership and Employee Performance: The Mediation Role of Psychological Empowerment Millennial Generation - Bustani; Asrid Juniar (Yayasan Ilomata, 2023)
This study investigates the influence of transformational leadership on the performance of millennial employees working in SMEs in Banjarmasin City in South Kalimantan Province, Indonesia. Furthermore, it postulates that psychological empowerment is a mediator in explicating the relationship between transformational leadership and employee performance. The research methodology employs a quantitative approach and purposive sampling to select a sample of 400 SME employees in Banjarmasin who were born between 1981 and 1996, thus belonging to the millennial generation. Data analysis involves the utilization of PLS-SEM, with the testing of constructs following a reflective-reflective model. The findings indicate that transformational leadership does not directly influence employee performance but instead exerts its influence through the mediating factor of psychological empowerment. Psychological empowerment, therefore, assumes a crucial role in mediating the relationship between these two constructs. Considering the limited existing literature concerning millennial generation workers, our model serves as a valuable tool for uncovering the distinctive traits of millennial employees within the SME context. Furthermore, this research lays the foundation for future cross-country comparisons of millennial leadership approaches across diverse Asian nations, contributing to a deeper understanding of the varying characteristics of the millennial generation within distinct cultural settings.